Solution 1123989
Solution 1123989
Solution 1123989
Class 12 - Mathematics
Section A
1
1. (a) 2
1 − cos x
Explanation: Given that y = tan − 1
√ 1 + cos x
x x
Using 1 - cos x = 2 sin2 2
and 1 + cos x = 2 cos2 2 , we obtain
x
√ ()
2sin 2 2 x x
y = tan − 1 x = tan − 1tan 2
= 2
2cos 2 2
2.
(c) n2y
Explanation: y1/n + y-1/n = 2x
Differentiating both sides we get
y1
n ( 1
y n −1 − y
−1
n −1
) =2
⇒
(
y1 y n − y
1 −1
n
) = 2ny
( ) ( y1
)
1 −1 1 −1 −1
y2 y n − y n + yn +y n −1 = 2ny 1
n
( ) ( )
2
1 −1 y1 1 −1
⇒ ny 2 y n − y n + y
yn + y n = 2n 2y 1
( )
1 −1
2
⇒ nyy 2 y n − y n + 2xy 1 = 2n 2yy 1
2ny 2
⇒ nyy 2 y1
+ 2xy 1 = 2n 2yy 1
n 2y 2y 2
⇒
2 + xy 1 = n 2y
y1
( )
1 −1 2
yn −y n
⇒ y2 4
+ xy 1 = n 2y
( )
1 −1 2
yn +y n −4
⇒ y2 + xy 1 = n 2y
4
4x 2 − 4
⇒ y2 + xy 1 = n 2y
4
1 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
y ( y − xlog y )
3. (a) x ( x − ylog x )
dy (
y y − xlog e y )
Hence dx
=
x ( x − ylog e x )
4.
log x
(c)
( 1 + log x ) 2
Explanation: xy = ex-y
Taking log on both sides,
log xy = log ex-y
y log x = x - y
y log x + y = x
x
y= log x + 1
Differentiate with respect to x,
1
dy ( log x + 1 ) − x × x
=
dx ( log x + 1 ) 2
dy ( log x + 1 ) − 1
=
dx ( log x + 1 ) 2
dy log x
=
dx ( log x + 1 ) 2
5.
(c) x √x
{ } 2 + log x
2√ x
⇒
dy
dx
dy
=y×
( ) 2 + log e x
2√ x
⇒
dx
= f ′(x)
= x √x
( ) 2 + log e x
2√ x
6. (a) x sin x
{ sin x + xlog x ⋅ sin x
x }
Explanation: Let y = f(x) = xsinx
2 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
Taking log both sides, we obtain
loge y = sin x loge x -(1) (Since loga bc = c loga b)
Differentiating (i) with respect to x, we obtain
1 dy 1
y dx
= sinx × x
+ log ex × cosx
⇒
dy
dx
=y× ( sin x
x
+ log excosx )
⇒
dy
dx
= f ′(x) = x sinx ( sin x + xlog xsin x
x )
.
Explanation:
1
⇒ y = sec − 1
( ) 1
2x 2 − 1
⇒ secy =
2x 2 − 1
⇒ cos y = 2x2 - 1
⇒ y = cos-1 (2x2 - 1)
Put x = cos θ ,we get
⇒ y =cos-1 (2cos2 θ - 1)
⇒ y =cos-1 (cos 2θ)
⇒ y = 2θ
But θ = cos-1 x, we get
dy (
d cos − 1 x )
⇒
dx
= dx
dy (
d cos − 1 x )
⇒ =2⋅
dx dx
⇒
dy
dx
dy
=2⋅
( )
−2
−1
√1 − x 2
⇒
dx
=
√1 − x 2
8.
−b
(d) a
3 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
9.
y
(b) x
x2 − y2
( ) x2 − y2
x2 + y2
= loga
⇒ = sinloga
x2 + y2
( x + y ) ( 2x − 2y ) ) ( 2x + 2y )
dy dy
2 2
dx (
− x2 − y2 dx
⇒ =0
(x +y )
2 2 2
dy dy dy dy
2x 3 − 2x 2y dx + 2xy 2 − 2y 3 dx − 2x 3 − 2x 2y dx + 2xy 2 + 2y 3 dx
⇒ =0
(x +y ) 2 2 2
dy
⇒ − 4x 2y dx + 4xy 2 = 0
dy
⇒ − 4x 2y dx = − 4xy 2
dy 4xy 2
⇒ =
dx 4x 2y
dy y
∴
dx
= x.
Which is the required solution.
10.
−1
(d) 2
( ) ( ( )( )
)
x x x x
x x cos 2 − sin 2 cos 2 + sin 2
cos 2 2 − sin 2 2
y = tan − 1 x x x x = tan − 1
cos 2 2 + sin 2 2 + 2sin 2 cos 2
( x
cos 2 + sin 2
x
) 2
x x
cos 2 − sin 2
⇒ y= tan − 1 x x
cos 2 + sin 2
x
Dividing by cos 2
in numerator and denominator, we get
x
1 − tan 2
y = tan − 1 x
1 + tan 2
Using tan ( ) π
4
−x =
1 − tan x
1 + tan x
, we obtain
y = tan − 1tan ( ) π
4
−
x
2
π x
= 4
− 2
Differentiating with respect to x, we
dy 1
dx
= − 2
4 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
Section B
11. Given that, y = sin − 1x + sin − 1 √1 − x2
Put, x = sin θ, we get
y = sin − 1(sinθ) + sin − 1(cosθ)
We have,
π
x ∈ (-1, 0) and x = sinθ ⇒ − 1 < sinθ < 0 ⇒ − 2
<θ<0
π π
∴ y = sin − 1(sinθ) + sin − 1(cosθ) = θ + 2
+θ= 2
+ 2sin − 1x
dy 2 2
⇒
dx
=0+ =
√1 − x 2 √1 − x 2
12. Let y = cos-1 (cot x)
Putting cot x = t, we get y = cos-1 t and t = cot x.
dy −1
Now, y = cos-1 t ⇒
dt
=
√1 − t 2
dt
And t = cot x ⇒
dx
= -cosec2 x
∴
dy
dx
= ( dy
dt
×
dt
dx ) =
cosec 2x
√1 − t 2
=
cosec 2x
√1 − cot 2 x
[ ∵ t = cot x]
cosec 2x
( ]
d
Hence, cos − 1(cotx) =
dx
√1 − cot 2 x
⇒ y = 2θ − π [ ∵
π
2
< 2θ < π ⇒ −
π
2
< 2θ − π < 0 ]
⇒ y = 2tan − 1x − π
dy 2 2
⇒ = −0=
dx 1 + x2 1 + x2
14. We have,
x = 3 sin t - sin 3t
dx
⇒
dt
= 3 cos t - 3 cos 3t .....(i)
And, y = 3 cos t - cos 3t
dy
⇒
dt
= -3 sin t + 3 sin 3t .....(ii)
dy ( dy / dt ) − 3sin t + 3sin 3t sin 3t − sin t
∴
dx
=
( dx / dt )
= 3cos t − 3cos 3t
= cos t − cos 3t
2cos 2tsin t
= 2sin 2tsin t
= cot 2t
d 2y dt − 2cosec 22t − 2cosec 22t
∴ = − 2cosec 22t ⋅ = = [from equation (i)]
dx 2 dx ( dx / dt ) 3 ( cos t − cos 3t )
5 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
∴
( )(
d 2y
dx 2
t= 3
π
)
=
− 2csc 2 ( 2π / 3 )
π
3cos 3 − cos π
= −2 ×
( ) 2
√3
2
⋅
3
1
( )
1
2 +1
= ( −2×
4
3
×
2
9 ) =
− 16
27
15. We have,
y = cos − 1{x√1 − x + √x 1 − x 2} √
⇒
√
y = cos − 1{x 1 − (√x) 2 + √x 1 − x 2} √
π
⇒ y= 2 √
− sin − 1{x 1 − (√x) 2 + √x 1 − x 2} √
{ } (√ )
π
⇒ y= 2
− sin − 1x + sin − 1√x [sin − 1 X 1 − Y 2 + Y 1 − X 2 √ = Sin-1X + Sin-1Y]
⇒ y= ( π
2
− sin − 1x − sin − 1√x )
⇒ y = cos − 1x − sin − 1√x
Differentiating with respect to x, we get
dy 1 1 d 1 1
dx
= − − dx
(√x) = − −
√ 1 − x2 √1 − ( √ x )2 √ 1 − x2 2√ x 1 − x 2
√
16. We have,
1
y=x+ 1
x+ 1
x+ x+ …
1
⇒ y=x+ y
⇒ y2 = xy + 1
dy dy
⇒ 2y dx = y + x dx + 0 [DIfferentiating both sides with respect to x]
dy
⇒
dx
(2y − x) = y
dy y
⇒
dx
= 2y − x
Hence proved.
17. We have,
x = sinθ, y = cos pθ
dy
dy dθ − psin pθ √
− p 1 − cos 2 pθ
∴
dx
= dx = cos θ
=
dθ
√1 − sin 2 θ
dy √
− p 1 − y2
⇒
dx
=
√1 − x 2
p2 1 − y2( )
⇒
()
dy 2
dx
=
(1−x ) 2
... [Squaring both sides]
(1 − x ) ( )
dy 2
⇒
2
dx
= p2 (1 - y2)
(1 − x )2 × 2
dy
dx
d 2y
dx 2
− 2x () (dy 2
dx
dy
= p 2 0 − 2y dx )
d 2y dy
⇒
(1 − x ) 2
dx 2
− x dx + p 2y = 0
6 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
Differentiating both sides with respect to x using chain rule,
d d
dx
(ex + y) = dx
(x)
d
⇒ ex + y dx
(x+y)=1
⇒ x 1+
[ ] dy
dx
= 1 [Using equation (i)]
dy 1
⇒ 1+ dx
= x
dy 1
⇒
dx
= x
-1
dy 1−x
⇒
dx
= x
19. Let, y = tan − 1( 1 + x 2 − x). √
Put x = cot θ, we get
( )
θ
( )
1 − cos θ 2sin 2 2
y = tan − 1(cosecθ − cotθ) = tan − 1 sin θ
= tan − 1 θ θ
2sin 2 cos 2
⇒ y = tan − 1 tan
( ) θ
2
=
1
2
θ=
1
2
cot − 1x [ x=cotθ ==> θ = cot-1x]
∴
dy
dx
=
1
2 ( ) −
1
1 + x2
= −
(
1
2 1 + x2 )
20. We have, y = x sin y .....(i)
Differentiating both sides with respect to x,
dy d
dx
= dx
(xsiny)
dy d d
⇒
dx
= x dx (siny) + siny dx (x) [using product rule]
dy dy
⇒
dx
= xcosy dx + siny(1) [using chain rule]
dy dy
⇒ − xcosy = siny
dx dx
dy
⇒
dx
(1 - x cos y) = sin y
dy sin y
⇒
dx
= ( 1 − xcos y )
⇒
dy
dx
= x ( 1 − xcos y )
y
[ ∵ siny =
y
x ]
21. Given: 2x + 3y = siny
d d d
⇒
dx
(2x) + dx
(3y) = dx
siny
dy dy
⇒ 2+3 = cosy
dx dx
dy dy
⇒ − cosy dx + 3 dx = − 2
dy
⇒ − dx
(cosy − 3) = − 2
dy 2
⇒
dx
= cos y − 3
22. It is given that
x = 2at2, y = at4
dx (
d 2at 2 )
Clearly, =
dt dt
( )
d t 2
= 2a dt
7 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
= 2a × 2t
= 4at ......(i)
dy
d at 4 ( )
And, =
dt dt
d t ( ) 4
=a dt
= a.4.t3
= 4at3 ......(ii)
Therefore, form equation (i) and (ii), we get
dy
dy dt 4at 3
dx
= dx = 4at
= t2
dt
dy
Hence, dx
= t2
=
1 + ( sec x + tan x )
1
2 ⋅
d
dx
(secx + tanx) ...
[ ∵
d
dx (tan x ) =
−1
1
1 + x2 ]
(secx )
1
= ⋅ ⋅ tanx + sec 2x
1 + sec 2 x + tan 2 x + 2sec x ⋅ tan x
1
= ⋅ secx ⋅ (secx + tanx)
( sec 2 x + sec 2 x + 2sec x ⋅ tan x )
1
= 2sec x ( tan x + sec x )
⋅ secx(secx + tanx)
1
= 2
⇒
du
dx
=u⋅ x⋅ [ 1
x
+ logx ⋅ 1 ]
du
⇒ = xx(1 + log x)
dx
And, log y = u log x
1 dy d d
⇒ ⋅ =u⋅ (log x) + (log x) ⋅ (u)
y dx dx dx
1 du
=u⋅ x
+ (logx) ⋅ dx
⇒
dy
dx
=y⋅ [ u
x
+ (logx) ⋅
du
dx ]
=x (x ) x
⋅
[ xx
x
+ (log x){xx(1 + log x)}]
=x (x ) x
⋅
[x (x−1) + xx (log x) + xx(log x)2]
25. Let y = √x + 1 − √x − 1 ........(1)
dy 1 1
So dx
= − ...........(2)
2√ x + 1 2√ x − 1
√x − 1 − √x + 1
=
√
4 x2 − 1
8 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
dy √x − 1 − √x + 1
dx
=
4 x2 − 1
√
d 2y
√x 2 − 1 ( 1
2√x − 1
−
1
2√x + 1 ) − ( √x − 1 − √x + 1 ) ×
x
√x 2 − 1
=
dx 2
(
4 x2 − 1 )
(
4 x2 − 1 )
d 2y
dx 2
= √x − 1 × √x + 1 ( 1
2√ x − 1
, −,
1
2√ x + 1 ) − (√x − 1 − √x + 1) ×
x
√x − 1 × √x + 1
(
4 x2 − 1 )
d 2y
dx 2
=
1
2
[√x + 1 − √x − 1] − x
( 1
√x + 1
, −,
1
√x − 1 )
d 2y y dy
(
4 x2 − 1 ) dx 2
= 2
− 2x dx
d 2y x dy y
(x 2 −1 ) dx 2
+ 2 dx
− 8
=0
26. Let, y = √ { ( )}
log sin
x2
3
−1
Put,
x2
3 ( )
− 1 = v, sin
x2
3
− 1 = sinv = u
x2
y = √z, z = log u, u = sin v and v = 3
−1
dy 1 dz 1 du dv 2x
∴
dz
= , du
= u
, dv
= cosv and dx
= 3
2√ z
dy dy dz du dv
Now, dx
= dz
× du
× dv
× dx
⇒
dy
dx
=
( )( ) ( )
2√ z
1 1
u
(cosv)
2x
3
=
x
3
×
cos v
u√log u
[ ∵ z = log u]
⇒
dy
=
x
×
( ) ( ) cos
x2
3 −1
=
xcot
x2
3 −1
dx 3
( )√ { ( ) } √ { ( ) }
2 2 x2
x x
sin 3 −1 log sin 3 −1 3 log sin 3 −1
9 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
d 2y d d 1
= (cot t) = cot t ×
dx 2 dx dt dx
dt
− cosec 2 t
= 3sin t cos 2t
d 2y − cosec 2 t
⇒ =
dx 2 3sin t cos 2t
28. According to the chain rule of differentiation
(
d y2 / b2 ) ( )
2
d y / b2
dy 2y dy
= × = ×
dx dy dx b2 dx
Therefore,
(
d x2 / a2 ) (
d y2 / b2 ) d(1)
dx
+ dx
= dx
2x 2y dy
+ × =0
a2 b2 dx
2x
−
dy a2
dx
= 2y
b2
dy − b 2x
=
dx a 2y
( )
√
( x − 3 ) x2 + 4
29. Let y =
( 3x + 4x + 5 )
2
1
y
⋅
dy
dx
=
1
2[ (x−3)
1
+
2x
x2 + 4
−
6x + 4
3x 2 + 4x + 5 ]
or
dy
dx
=
y
2 [ 1
(x−3)
+
2x
x2 + 4
−
6x + 4
3x 2 + 4x + 5 ]
( )
√ [ ]
( x − 3 ) x2 + 4
dy 1 1 2x 6x + 4
⇒ = + −
dx 2 3x 2 + 4x + 5 (x−3) x2 + 4 3x 2 + 4x + 5
30. We have,
x = a(θ + sin θ) and y = a(1 - cos θ)
dx dy
⇒
dθ
= a(1 + cos θ) and dθ
= a sin θ
dy ( dy / dθ )
⇒
dx
=
( dx / dθ )
asin θ sin θ 2sin ( θ / 2 ) cos ( θ / 2 ) θ
= a ( 1 + cos θ )
= ( 1 + cos θ )
= 2 = tan 2
2cos ( θ / 2 )
⇒
d 2y
dx 2
=
d
dx ( )
tan 2
θ 1
= 2 sec 2 2
θ
⋅
dθ
dx
= ( 1
2
θ
sec 2 2 ) ×
1
a ( 1 + cos θ )
⇒
( )
d 2y
dx 2
θ= 2
π
,= sec 2
1
2
π
4
⋅
(
a 1 + cos 2
1
π
)
=
1
2
(√2)2
1
a(1+0)
=
1
a
Section C
31. Given, y = 2sin x + 3cos x ...(i)
d 2y
As we have to prove: +y=0
dx 2
To prove the above we will find differentiation two times .
10 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
As
d 2y
dx 2
=
d
dx () dy
dx
[ ∵
d
dx
(sinx) = cosx& dx (cosx) = − sinx
d
]
= 2cos x - 3 sinx
dy
∴ = 2cos x - 3sin x
dx
Differentiating again with respect to x:
d
dx () dy
dx
=
d
dx
(2cosx − 3sinx) =
2d
dx
cosx − 3 dx sinx
d
d 2y
= -2 sin x - 3cos x
dx 2
From equation (i) we can write:
y = 2sin x + 3cos x
d 2y
∴ = -(2sin x + 3cos x) = -y
dx 2
d 2y
∴ +y=0
dx 2
Hence proved.
32. According to the question, x = a cos3 θ and y = a sin3 θ
d 2y π
We are required to find the value of at θ =
dx 2 6
Therefore,on differentiating both sides of x and y w.r.t θ ,we get,
dx d
dθ
= 3acos 2θ dθ (cosθ)
= 3acos 2θ ⋅ ( − sinθ)
= − 3acos 2θ ⋅ sinθ
dy d
and = 3asin 2θ (sinθ)
dθ dθ
= 3asin 2θ ⋅ (cosθ) = 3asin 2θ ⋅ cosθ
Now,
dy
dx
=
( ) dy / dθ
dx / dθ
3asin 2 θ ⋅ cos θ
= = − tanθ
− 3acos 2 θ ⋅ sin θ
Again, On differentiating both sides w.r.t x, we get,
d 2y d d dθ
= ( − tanθ) = − (tanθ) dx
dx 2 dx dθ
dθ
= − sec 2θ ⋅
dx
= − sec 2θ ⋅
π
( 3acos 2
−1
θ ⋅ sin θ ) (
=
3acos 4
1
θ ⋅ sin θ )
∴ At θ = 6
( ) d 2y
dx 2
atθ = 6
π
=
( )( )
3a cos 6
π
1
4
sin 6
π
11 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
1
=
( )( )
√3 4 1
3a 2 2
1 32
= =
27a
3a
( )( )
9
16
1
2
⇒
dy
dx
=n x+ ( √1 + x 2 )
n−1
( 1+
) √
2 1 + x2
2x
[ Using chain rule of derivative]
( ) √1 + x 2
x+
( )
dy
2 n−1
⇒
dx
=n x+ √1 + x √1 + x 2
dy (
n x+ √1 + x 2 )
n
⇒
dx
=
√1 + x 2
dy ny
⇒
dx
= [ From Equation(i)]
√1 + x 2
dy
⇒
√1 + x 2 dx = ny.........(ii)
Differentiating both sides w.r.t x again,
d 2y 2x dy dy
⇒
√ 1 + x2
dx 2
+
2 √ 1 + x2
. dx
= n dx
d 2y dy dy
⇒
(1 + x ) 2
dx 2
+ x dx = n ⋅ √1 + x 2 dx [ multiplying both sides by √1 + x 2]
d 2y dy ny
⇒
(1 + x ) 2
dx 2
+ x dx = n 1 + x 2 ⋅√ √1 + x 2
[ From Equation(ii)]
d 2y
(1 + x )
dy
∴
2 + x dx = n 2y
dx 2
Hence Proved
34. We have, tan(x + y) + tan(x - y) = 1
Differentiating with respect to x, we get,
d d d
⇒
dx
tan(x + y) + dx
tan(x − y) = dx
(1)
d d
⟹ sec 2(x + y) dx (x + y) + sec 2(x − y) dx (x − y) = 0
⇒ sec 2(x + y) 1 + [ ] dy
dx
+ sec 2(x − y) 1 − [ ] dy
dx
=0
dy dy
⇒ sec 2(x + y) − sec 2(x − y) = -[sec2(x + y) + sec2(x - y)]
dx dx
dy
⇒
dx
[sec2(x + y) - sec2(x - y)] = -[sec2(x + y) + sec2(x - y)]
dy sec 2 ( x + y ) + sec 2 ( x − y )
⇒ =
dx sec 2 ( x − y ) − sec 2 ( x + y )
35. xy ⋅ yx = xx
⇒ y log x + x log y = x log x (taking log both sides)
differentiate both sides w.r.t. x, we get
⇒
( y⋅
1
x )(
+ logx ⋅
dy
dx
+ x⋅
1
y
⋅
dy
dx
+ logy ⋅ 1 =x ⋅
) 1
x
+ logx ⋅ 1
⇒
y
x
+ log
() (
y
x
− 1 =− logx +
x
y ) ⋅
dy
dx
12 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
dy
y
1 − x − log () y
x
⇒
dx
= x
log x + y
or
y
x [ x + xlog x − y − xlog y
ylog x + x ]
sin − 1 x d 2y
( )
dy
36. According to the question, if y = , then we have to show that 1 − x 2 − 3x dx − y = 0.
√1 − x 2 dx 2
sin − 1 x
Now,we have, y =
√1 − x 2
Therefore,on differentiating both sides w.r.t x, we get,
d d
dy √1 − x 2 × dx ( sin − 1 x ) − ( sin − 1 x ) × dx √1 − x 2
dx
=
(√ ) 1 − x2
2
=
[ √1 − x 2 × √1 − x
1
2
− sin − 1x .
2√
1
1 − x2
⋅
d
dx (1−x ) 2
]
(√ ) 1 − x2
2
=
[√ 1 − x2 ⋅
√
1
1 − x2
(
− sin − 1x ) ⋅
√
− 2x
2 1 − x2 ]
1 − x2
xsin − 1 x
1+
√1 − x 2
=
(1−x ) 2
dy 1 + xy
⇒ =
dx 1 − x2
(1 − )
dy
⇒ x2 = 1 + xy
dx
Therefore,on differentiating both sides of above equation w.r.t x, we get,
(1 − x ) ( ) (1 − x ) =
d dy dy d d
2 2
⋅
dx dx
+ dx ⋅
dx dx
(1 + xy) [By using product rule of derivative]
d 2y
(1 − x )
dy dy
2
⇒ + ( − 2x) = 0 + x dx + y.1
dx 2 dx
d 2y
(1 − x )
dy dy
2
⇒ − 2x dx − x dx − y = 0
dx 2
d 2y
(1 − x )
dy
∴
2 − 3x −y=0
dx 2 dx
[ √( ) √( )
][
x x 2 x x 2
)]
cos 2 + sin 2 + cos 2 − sin 2
√( x
cos 2 + sin 2
x
) √(2
−
x
cos 2 − sin 2
x
) 2
x x x x
cos 2 + sin 2 + cos 2 − sin 2
= cot − 1 x x x x
cos 2 + sin 2 − cos 2 + sin 2
( )
x
2cos 2
= cot − 1 x
2sin 2
13 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
= cot − 1 cot 2 ( ) x
x
=
2
x
y= 2
dy 1
dx
= 2
(e ) + (10 ) + (e )
dy d d d
= x x xlog x
dx dx dx dx
d
= e x + 10 xlog10 + e xlog x (xlogx)
dx
[
= e x + 10 xlog10 + e xlog x x dx (logx) + logx dx (x)
d d
]
= e x + 10 xlog10 + e log x x
x
[() ] 1
x
+ logx
{
− log ex, for 0 < x < 1
|
f(x) = log ex = | log ex, for x ≥ 1
Clearly, f(x) is differentiable for all x > 1 as well as for all x < 1.
So, we have to check its differentiability at x = 1.
We have,
f(x) −f(1)
(LHD at x = 1) = lim x−1
x→1−
− log x − log 1
⇒ (LHD at x = 1) = lim x−1
.... [ ∵ f(x) = − log xx for 0 < x < 1]
x→1−
log x
⇒ (LHD at x = 1) = − lim x−1
x→1−
log ( 1 − h ) log ( 1 − h )
= − lim 1−h−1
= − lim −h
= −1
h→0 h→0
and,
f(x) −f(1)
(RHD at x = 1) = lim
x−1
x→1+
log x − log 1 log ( 1 + h ) log ( 1 + h )
⇒ (RHD at x = 1) = lim x−1
= lim 1+h−1
= lim h
=1
x→1+ h→0 h→0
Clearly, (LHD at x = 1) ≠ (RHD at x = 1).
So, f (x) is not differentiable at x = 1
40. Given, y 2 + ()
dy 2
dx
= a2 + b2.......(i)
dy
We shall first find dx
and then use it in L.H.S of (i).
Now, y = a sin x + b cos x..........(ii)
Therefore,on differentiating both sides of Eq.(ii) w.r.t x, we get,
14 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
dy
dx
= a cos x - b sin x
Now, let us take LHS of Eq.(i),
Here, LHS = y2 +
()
dy 2
dx
{
x, if x ∈
[ ] 0,
π
2
y = sin − 1(sinx) = π − x, if x ∈
[ ]π 3π
2
, 2
− 2π + x, if x ∈
[ ] 3π
2
, 2π
We observe that
( LHD at x =
π
2 ) = 1 and RHD at x =
( π
2 ) = −1
( LHD at x =
3π
2 ) = − 1 and
( RHD at x =
3π
2
π 3π
) =1
{
1, it x = 0,
[ ) 2
x
∴
dy
dx
= − 1, 4x =
( )
π 3π
2
, 2
1, is x ∈
( )
3π
2
, 2x
[
y = θ since sin − 1(sinθ) = θ, if θ ∈
[ − 2,
π π
2 ]]
y = cos − 1x[ since x = cosθ]
15 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
Differentiating it with respect to x,
dy 1
dx
= −
√1 − x 2
43. Let, y = sin-1{1 - 2x2)
put x = sin θ
⇒ {
y = sin − 1 1 − 2sin 2θ }
⇒ y= sin − 1(cos2θ)
⇒ y = sin − 1 sin { ( )} π
2
− 2θ ...(i)
π
⇒ 0<θ< 2
⇒ 0 < 2θ < π
⇒ 0 > − 2θ > − π
⇒
π
2
>
( ) π
2
− 2θ >
π
2
−π
⇒
π
2
> ( ) π
2
− 2θ > −
π
2
⇒ −
π
2
<( ) π
2
− 2θ <
π
2
y=
π
2 [
− 2θ since , sin − 1(sinθ) = θ, if θ ∈
[ π π
− 2, 2 ]]
π
⇒ y= 2
− 2sin − 1x[ since , x = sinθ]
Differentiating it with respect to x,
dy
dx
dy
=0−2
( )
2
1
√1 − x 2
dx
= −
√1 − x 2
44. We have, x√1 + y + y√1 + x = 0
⇒ x√ 1 + y = − y√ 1 + x
Squaring both sides, we get,
⇒ (x 1 + y)
2 = ( − y 1 + x) 2
√ √
⇒ x2(1 + y) = y2(1 + x)
⇒ x2 + x2y = y2 + y2x
⇒ x2 - y2 = y2x - x2y
⇒ (x - y)(x + y) = xy(y - x)
⇒ (x + y) = -xy
⇒ y + xy = -x
⇒ y (1 + x) = -x
−x
⇒ y= (1+x)
Differentiating with respect to x, we get
16 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
[ ]
d d
dy − ( 1 + x ) dx ( x ) − ( − x ) dx ( x + 1 )
⇒ =
dx ( 1 + x )2
⇒
dy
dx
=
[ ]
− (1+x) (1) +x(1)
( 1 + x )2
⇒
dy
dx
dy
=
[ ] −1−x+x
( 1 + x )2
−1
⇒ =
dx ( 1 + x )2
dy
⇒ (1 + x) 2 dx = − 1
dy
⇒ (1 + x) 2 dx + 1 = 0
LHS=RHS
Hence Proved.
45. According to the question, x py q = (x + y) p + q
Taking log both side
⇒ plogx + qlogy = (p + q)log(x + y)
⇒
p
x
+ y.
q dy
dx
= (p + q). ( )
(x+y)
1
1+
dy
dx
+ log(x + y). (0)
⇒
p
x
+ .
q dy
y dx
=
(p+q)
(x+y) ( )
1+
dy
dx
⇒
dy
dx ( q
y
−
p+q
x+y ) =
p+q
x+y
−
p
x
⇒
dy
dx [ qx + qy − py − qy
y(x+y) ] =
px + qx − px − py
(x+y) .x
⇒
dy
dx [ qx − py
y(x+y) ] =
qx − py
(x+y) .x
dy y
⇒
dx
= x
π 3π
46. We have, y = (sin x - cos x)(sin x - cos x), 4
<x< 4
,
Therefore, on taking logarithm both sides, we get,
log y = log (sin x - cos x)(sin x - cos x),
⇒ log y= (sin x - cos x). log(sin x - cos x)
17 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
47. Let u = tan − 1
( ) √1 − x 2
x
du
and v = cos − 1(2x 1 − x 2). √
du dx
We want to find dv
= dv
dx
Now u = tan − 1
( ) √1 − x 2
x
. Put x = sinθ ⋅ ( π
4
<θ<
π
2 )
Then u = tan − 1
( ) √1 − sin 2 θ
sin θ
= tan − 1(cotθ)
= tan − 1 tan { ( )} π
2
−θ =
π
2
−θ=
π
2
− sin − 1x
du −1
Hence dx
=
√1 − x 2
Now v = cos − 1(2x 1 − x 2) √
π
= 2
− sin − 1(2x 1 − x 2) √
π π
= 2
− sin − 1(2sinθ 1 − sin 2θ) = √ 2
− sin − 1(sin2θ)
=
π
2
− sin − 1{sin(π − 2θ)} [ since
π
2
< 2θ < π ]
π −π
= 2
− (π − 2θ) = 2
+ 2θ
−π
⇒ v= 2
+ 2sin − 1x
dv 2
⇒
dx
=
√1 − x 2
−1
du
du dx √1 − x 2 −1
Hence dv
= dv = 2 = 2
dx
√1 − x 2
48. To find: value of cos-1( 1 − x 2) √
The formula used cos θ = sin
( ) n
2
−θ
(
d sin − 1 x ) 1
dx
=
√1 − x 2
We have, cos-1 ( 1 − x 2) √
Putting x = sin θ
θ = sin-1 x ......(i)
Putting x = sin θ in the equation
⇒
√
cos-1( 1 − (sinθ) 2)
⇒ cos-1 ( √1 − sin2θ)
⇒ cos-1 (cos θ)
⇒ θ
Now, we can see that cos-1 ( 1 − x 2) = θ √
⇒ θ= sin-1 x
18 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
d(θ)
⇒
dx
d
= dx (sin x ) −1
1
= .
√1 − x 2
√a 2 − x 2 }
Put x = a sin θ
⇒ y = tan − 1
{ a+
asin θ
√a 2 − a 2sin 2 θ }
⇒ y = tan − 1
( a+
asin θ
√a 2 ( 1 − sin 2 θ ) )
⇒ y = tan − 1
{ asin θ
a + acos θ }
⇒ y = tan − 1 { asin θ
a ( 1 + cos θ ) }
⇒ y = tan − 1 { sin θ
1 + cos θ }
{ }
θ θ
2sin 2 cos 2
⇒ y = tan − 1 θ
2cos 2 2
⇒ y = tan − 1 tan 2
( ) θ
...(i)
y=
θ
2 [ since , tan − 1(tanθ) = θ, if θ ∈
[ π π
− 2, 2 ]]
⇒ y=
1
2
sin − 1 () x
a
[Since, x = a sin θ]
√ ()1−
x
a
2
⇒
dy
dx
=
2 √
a
a2 − x2
×
() 1
a
19 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
dy 1
∴
dx
=
√
2 a2 − x2
As
d 2y
dx 2
= dx
d
() dy
dx
[ d
dx
tan − 1x =
1 + x2
1
]
And y = et
dy dy dt
dx
= dt dx
−1
dy 1 e tan x
= et = ...(ii)
dx 1 + x2 1 + x2
Again differentiating with respect to x applying product rule:
d 2y
dx 2
= e tan
−1 x
d
dx ( ) 1
1 + x2
+
1
1 + x2
d
dx
e tan
−1 x
( )
−1 −1
d 2y e tan x
2xe tan x
= −
dx 2
(1+x ) 2 2
(1+x ) 2 2
(x ) = nx
d d 1
[using equation (ii); n n − 1& tan − 1x = ]
dx dx 1 + x2
d 2y tan − 1 x tan − 1 x
( )
e 2xe
1 + x2 = −
dx 2 1 + x2 1 + x2
−1
d 2y e tan x
(1 + x ) 2
dx 2
=
1 + x2
(1 − 2x)
∴ (1 + x2) y2 + (2x - 1) y1 = 0
Hence proved
51. Given,
y = (log(x + √x2 + 1)) 2
⇒
dy
dx
= 2(log(x + √x2 + 1)) x + √x + 1
1
2 ( 1+
√
1
2 x2 + 1
(2x)
)
20 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
⇒
dy
dx
= 2(log(x + √x2 + 1)) x + √x + 1
1
2 ( ) 1+
x
√x 2 + 1
( ) √x 2 + 1
dy 1 x+
⇒
dx
= 2(log(x + √ x2 + 1))
x+ √x 2 + 1 √x 2 + 1
dy
2 ( log ( x + √x 2 + 1 )
⇒ =
dx
√x 2 + 1
( )
x
1+
√1 + x 2 x
2
x + √1 + x 2
× √1 + x 2 − 2 ( log ( x + √1 + x 2 ) ) ×
√1 + x 2
d 2y
⇒ =
dx 2
(√ ) 1 + x2
2
⇒
d 2y
=
2
( )√
√
1
1 + x2
× 1 + x 2 − 2 ( log ( x + √1 + x 2 ) ) × √1 + x
x
2
dx 2
(1+x ) 2
2
2 − 2 ( log ( x + √1 + x 2 ) ) × √1 + x 2
d y
⇒ =
dx 2
(1+x ) 2
(
d sin − 1 x ) 1
dx
=
√1 − x 2
We have, sin-1(2x 1 − x 2) √
Putting x = sin θ
θ = sin-1 x .....(i)
Putting x = sin θ in the equation
⇒
√
sin-1 (2sinθ 1 − (sinθ) 2)
21 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
⇒ 2 sin-1 x
Now, we can see that sin-1 (2x 1 − x 2) = 2 sin-1 x √
Now Differentiating
d2θ (
d 2sin − 1 x )
⇒
dx
= dx
( )
d
= 2 dx sin − 1x
2
=
√1 − x 2
53. According to the question, if, y = sin − 1 x√1 − x − √x 1 − x 2 . [ √ ]
We have to find the derivative of y w.r.t x.We shall make use of the substitution to find the derivative.
[
y = sin − 1 sinϕ 1 − sin 2θ − sinθ 1 − sin 2ϕ
√ √ ]
⇒ y = sin − 1[sinϕcosθ − sinθcosϕ] [ ∵
√1 − sin2x = cosx ]
⇒ y = sin − 1sin(ϕ − θ)[ ∵ sinϕcosθ − cosϕsinθ = sin(ϕ − θ)]
dy
dx
=
√1 − x 2
dy
1
−
1
√ 1 − ( √x ) 2
1 1
×
d
dx √
( x)
1
[ ∵
d
dθ (sin θ ) = √
−1
1
1 − θ2 ]
⇒
dx
= − ⋅
√ 1 − x2 √1 − x 2√ x
dy 1 1
Hence, = −
dx
√1 − x 2 √
2 x − x2
1
54. y = a t + t
dy
dt
1
= a t + t . loga. 1 −
( ) 1
t2
x= t+ ( ) 1 a
t
dx
dt ( )
=a t+
1 a−1
t
. 1−
( ) 1
t2
dy
=
( ) 1
a t + t . log a 1 −
t2
1
dx
( ) ( )
a t+ t
1 a−1
1−
1
t2
1
a t + t . log a
=
( )
a t+ t
1 a−1
22 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
55. We have, x13y7 = (x + y)20
Taking log on both sides,
log(x13y7) = log(x + y)20
⇒ 13 log x + 7 log y = 20 log(x + y)
Differentiating with respect to x using chain rule,
d d d
13 dx (log x) + 7 dx
(log y) = 20 dx
log (x + y)
13 7 dy 20 d
⇒ + = (x + y)
x y dx x + y dx
⇒
13
x
7 dy
+
7 dy
y dx
20 dy
=
20
x+y [ ] 1+
20
dy
dx
13
⇒
y dx
− x + y dx
= x+y
− x
⇒
dy
dx [ 7
y
−
20
x+y ] =
20
x+y
−
13
x
⇒
dy
dx [ ] [
7 ( x + y ) − 20y
y(x+y)
=
20x − 13 ( x + y )
x(x+y) ]
⇒
dy
dx
=
[ ][
20x − 13x − 13y
x(x+y)
y(x+y)
7x + 7y − 20y ]
⇒
dy
dx
=
y
x ( ) 7x − 13y
7x − 13y
dy y
⇒
dx
= x
2t
56. Here, sinx = .... (i)
1 + t2
2t
And tany = .... (ii)
1 − t2
∴
d
dx
sinx dt =
dx d
dt ( ) 2t
1 + t2
(1+t ) ( )
d d
2 ⋅ ( 2t ) − ( 2t ) ⋅ dt 1 + t 2
dx dt
⇒ cosx dt =
(1+t ) 2 2
(
2 1 + t 2 − 2t ⋅ 2t) 2 + 2t 2 − 4t 2
= =
(1+t ) 2 2
(1+t ) 2 2
2 (1−t ) 2
dx 1
⇒
dt
= ⋅
cos x
(1+t ) 2 2
2 (1−t ) 2
( )
2 1 − t2
dx 1 1
⇒
dt
= ⋅ = ⋅
(1+t ) √1 − sin 2
(1 + t )
√ ( )
2 2 x 2 2
2t 2
1−
1 + t2
dx ( ) (1+t )
2 1 − t2 2
2
= ⋅ = ..... (iii)
dt 1 + t2
(1 + t ) ( 1 − t )
2 2 2
Also,
d
dy
tany ⋅
dy
dt
=
d
dt ( ) 2t
1 − t2
(1 − t ) ( )
d d
2 ⋅ ( 2t ) − 2t ⋅ dt 1 − t 2
dy dt
sec 2y dt =
(1 − t ) 2 2
23 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
dy 2 − 2t 2 + 4t 2 1
dt
= ⋅
2
( 1 − t ) sec y 2 2
2 (1+t ) 2
(
2 1 + t2 )
1 1
= ⋅ = ⋅
( 1 − t ) ( 1 + tan y )
2 2 2
(1−t ) 2 2
1+
4t 2
(1−t ) 2 2
(
2 1 + t2 ) (1−t ) 2 2
2
= ⋅ = .... (iv)
1 + t2
( 1 − t2 ) (1+t )
2 2 2
dy dy / dt 2 / 1 + t2
∴ = = = 1 [from eqs. (iii) and (iv)]
dx dx / dt 2 / 1 + t2
[ √
]
6x − 4 1 − 4x 2
57. Given y = sin − 1 5
1
Put, x = 2 sinθ
[ √ ( )
]
sin θ sin θ 2
6× 2 −4 1−4× 2
Therefore, y = sin − 1 5
( )
3sin θ − 4 1 − sin 2 θ √
= sin − 1 5
9 16 4
=
√ 1− 25
=
√ 25
= 5
24 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
58. ATQ , x = cos − 1
( ) √1 + t 2
1
⇒
dx
dt
=
√ ( ) 1−
−1
1 2
d
dt ( )
√1 + t 2
1
√1 + t 2
⇒
dx
dt
=
√ 1−
−1
(1+t )
1
1
2
{ } (
2 1 + t2
−1
)
3
2
d
dt (1 + t )
2
dx ( 1 + t2 ) 2
1
⇒
dt
= × 3 (2t)
√1 + t 2 − 1 (
2 1 + t2 ) 2
dx t
⇒ =
dt
√t2 × ( 1 + t2 )
dx 1
⇒ = ...(i)
dt 1 + t2
Now, y = sin − 1
( ) √1 + t 2
1
⇒
dy
dt
=
√ ( ) 1−
1
1 2
d
dt ( )
√1 + t 2
1
√1 + t 2
⇒
dy
dt
=
√ 1−
1
(1+t )
1
1
2
{ } (
2 1 + t2
−1
)
3
2
d
dt (1 + t )
2
dx (1+t ) 2 2
−1
⇒
dt
= × 3 (2t)
√1 + t 2 − 1 (
2 1 + t2 ) 2
dx −1
⇒
dt
= (2t)
√
2 t2 × 1 + t2 ( )
dx −1
⇒ = ...(ii)
dt 1 + t2
Dividing equation (ii) by (i),
dy
dt 1 (1+t ) 2
dx = × −1
dt ( 1+t ) 2
dy
⇒
dx
= −1
√1 − x 2
Put x = sin θ
25 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
y = tan − 1
{ 1+
sin θ
√1 − sin 2 θ }
y = tan − 1 ( sin θ
1 + cos θ )
{ }
θ θ
2sin 2 cos 2
y = tan − 1 θ
2cos 2 2
y = tan − 1 tan 2
{ } θ
...(i)
π π
⇒ − 2
<θ< 2
π θ π
⇒ − 4
< 2
< 4
So, from equation (i),
y=
θ
2
1
[ Since tan − 1(tanθ) = θ, if θ ∈
[ π π
− 2, 2 ]]
y= 2
sin − 1x [Since, x = sin θ]
Differentiating it with respect to x,
dy 1
dx
=
2 1 − x2
√
60. We have, y = e 3x × sin4x × 2 x ...(i)
Taking log on both sides,
log y = log e3x + log sin 4x + log 2x
⇒ log y = 3x log e + log sin 4x + x log 2
26 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
θ
1 + cos θ = 2 cos2 2
⇒ cot-1
( 1
sin x
+
cos x
sin x )
⇒ cot-1
( 1 + cos x
sin x )
( )
x
2cos 2 2
⇒ cot-1 sin x
( )
x
2cos 2 2
⇒ cot-1 x x
2sin 2 cos 2
()
x
cos 2
⇒ cot-1 x
sin 2
⇒ cot-1 cot
( ) x
2
x
⇒
2
x
Now, we can see that cot-1(cosec x + cot x) = 2
Now, differentiating,
⇒
d
dx ()
x
2
1
⇒
2
1 + cos 3x
63. We have, cot-1 (
√ 1 − cos 3x
)
1 + cos 3x
√
⇒ cot-1 ( 3x )
2sin 2 2
1 + cos 3x
√
⇒ cot-1 ( 3x )
2sin 2 2
3x
√
2cos 2 2
⇒ cot-1 ( 3x )
2sin 2 2
⇒
√ ()
cot-1 ( cot 2
3x
2
)
⇒ cot-1 cot( ( )) 3x
2
27 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
3x
⇒
2
1 + cos 3x 3x
Now, we can see that cot-1 (
√ 1 − cos 3x
)= 2
Now, differentiating,
⇒
d
dx () 3x
2
3
=
2
64. Given,
y = a (θ + sinθ) ...(i)
x = a (1 + cosθ) ...(ii)
d 2y 1 π
To prove: = − at θ =
dx 2 a 2
To prove above equation we need to find double derivative of function y wrt x .
As,
d 2y
dx 2
=
d
dx ()
dy
dx
Similarly,
dx d
dθ
= dθ
a(1 + cosθ) = − asinθ ...(iv)
[ ∵
d
dx
cosx = − sinx,
dy
d
dx
sinx = cosx ]
dy dx a ( 1 + cos θ ) ( 1 + cos θ )
∴
dx
= dx = − asinθ
= − sin θ
...(v)
dθ
d 2y 1
= − {cscθ( − sinθ) + (1 + cosθ)( − cscθcotθ)} [using equation (iv)]
dx 2 ( − asinθ )
d 2y
{ − 1 − cscθcotθ − cot θ}
1
= 2
dx 2 asin θ
d 2y 1 π
As we have to find = − at θ =
dx 2 a 2
∴ put θ = π / 2 in above equation:
{ }
2
d y π π π 1 { −1−0−0}1
2 = − 1 − csc 2 cot 2 − cot 2 2 π = a
dx asin 2
d 2y 1
= −
dx 2 a
65. We have,
x5 + y5 = 5xy
Differentiating with respect to x, we get
d d d
dx (x ) + (y ) =
5
dx
5
dx
(5xy)
⇒
dy
5x 4 + 5y 4 dx = 5 x dx + y dx (x) [ dy d
]
⇒
dy
5x 4 + 5y 4 dx = 5 x dx + y(1) [ dy
]
28 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
dy dy
⇒ 5x 4 + 5y 4 dx = 5x dx + 5y
dy dy
⇒ 5y 4 − 5x = 5y − 5x 4
dx dx
dy
⇒ 5 dx (y4 - x) = 5(y - x4)
dy ( )
5 y − x4
⇒ =
dx
5 (y −x ) 4
dy y − x4
⇒ =
dx y4 − x
The differentiation of the given function y is as above.
Section D
66. y = 3cos(log x) + 4 sin(log x)
Diff. both side w.r.t. to x
− 3sin ( log x ) 4cos ( log x )
y1 = x
+ x
xy1 = -3sin(log x) + 4cos(logx)
Again diff.
− 3cos ( log x ) 4sin ( log x )
xy 2 + y 1.1 = x
− x
x2y2 + xy1 = -y
x2y2 + xy1 + y = 0
x2 + 1
√
dy
67. We have, dx
, if y = x tan x + 2
x2 + 1
Taking, u = x tan x and v =
√ 2
⇒
du
dx
=u
[ tan x
x
+ logx. sec 2x
]
= x tan x
[ tan x
x
+ logx. sec 2x ...(iv)
]
also, differentiating Eq. (iii) w.r.t. x, we get
dv 1 dv 1
2v. dx
= 2
(2x) ⇒
dx
= 4v
. (2x)
dv 1 x . √2
⇒
dx
= .2x =
√
2 x2 + 1
√
x2 + 1
4. 2
dv x
⇒ = ...(v)
dx
√2 ( x 2 + 1 )
Now, y = u + v
dy du dv
∴
dx
= dx
+ dx
= x tan x [ tan x
x
+ logx. sec 2x + ] x
√2 ( x 2 + 1 )
29 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
68. Let u = sin − 1( 1 − x 2)√
Put x = cosθ
⇒ θ = cos-1x
We get, u = sin-1(sin θ) ...(i)
Let v = cot − 1
( ) x
√1 − x 2
⇒ v = cot − 1
( ) cos θ
√1 − cos 2 θ
⇒ v = cot − 1
( )
cos θ
sin θ
⇒ v = cot-1(cot θ) ....(ii)
Here,
0<x<1
⇒ 0 < cos θ < 1
π
⇒ 0<θ< 2
So, from equation (i),
[
u = θ since, sin − 1(sinθ) = θ, if θ ∈
[ π π
− 2, 2 ]]
⇒ u = cos-1x
Differentiating it with respect to x,
du −1
dx
= ...(iii)
√1 − x 2
From equation (ii),
[
v = θ since , cot − 1(cotθ) = θ, if θ ∈ (0, π) ]
⇒ v = cos-1x
Differentiating it with respect to x,
dv −1
dx
= ...(iv)
√1 − x 2
Dividing equation (iii) by (iv)
( )( )
du
dx −1 √1 − x 2
dv = −1
dx √1 − x 2
du
∴
dv
= 1.
69. x = a(cosθ + θ. sinθ)
dx
dθ
= a[− sinθ + θ. cosθ + sinθ.1]
dx
dθ
= aθ. cosθ ...(1)
y = a(sinθ − θ. cosθ)
dy
dθ
= a[cosθ − (− θsinθ + cosθ.1)]
= a[cosθ + θ. sinθ − cosθ]
= aθ. sinθ ...(2)
(2) ÷ (1)
dy a θ . sin θ
dx
= a θ . cos θ
= tanθ
30 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation
(
70. x = a cost + logtan 2
t
)
dx
dt
[
= a − sint +
tan 2
1
t
. sec 2 .
t
2 2
1
[ ]
= a − sint +
1
sin
cos
t
2
2
t
×
1
cos 2 2
t ×
1
2
[
= a − sint + t
2sin 2 . cos 2
1
t
]
[
= a − sint +
1
sin t ]
=a
[ ] − sin 2t + 1
sin t
=a
dx
[ ] cos 2t
sin t
cos 2t
=a
dt sin t
y = a sin t
dy
= acost
dt
dy acos t sin t
dx
= 2 = cos t
cos t
a sin t
dy
dx
= tant
31 / 31
9830284417amalesh1977.wixsite.com/pradhaneducation